2011
DOI: 10.1080/03601234.2011.559893
|View full text |Cite
|
Sign up to set email alerts
|

Determination of dimethyl fumarate (DMFu) in silica gel pouches using gas chromatography coupled ion trap mass spectrometry

Abstract: A simple method for the determination of dimethyl fumarate (DMFu) in silica gel pouches has been developed. The gas chromatographic behaviour of DMFu was investigated; the instrumental method, based on EI mass spectrometry coupled with an Ion Trap Detector operating whether in full scan mode or in MS/MS mode was also investigated. Several factors have been evaluated and optimized during the development process: solvent and temperature of extraction, type of stationary phase in capillary column. The analytical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Description : the methyl ester form of fumaric acid and an extremely potent irritant and sensitizer [ 141,142 ] used in desiccant and anti-mold sachets/pouches [ 143,144 ] . In addition, a mixture of fumaric acid esters has been used as an oral treatment of psoriasis [ 142 ] .…”
Section: Dimethyl Fumarate (Dmf)mentioning
confidence: 99%
“…Description : the methyl ester form of fumaric acid and an extremely potent irritant and sensitizer [ 141,142 ] used in desiccant and anti-mold sachets/pouches [ 143,144 ] . In addition, a mixture of fumaric acid esters has been used as an oral treatment of psoriasis [ 142 ] .…”
Section: Dimethyl Fumarate (Dmf)mentioning
confidence: 99%
“…DMF is non-official in BP, EP [2][3] and United States Pharmacopeia (USP) [4]. Literature review showed that few analytical methods have been described for the estimation of DMF including spectrophotometric [5][6], gas chromatography (GC) [7][8][9][10][11], high performance liquid chromatography (HPLC) [12][13][14][15][16][17], electrochemical and voltammetric methods [18] have been reported for the estimation of DMF in pure or in dosage forms.…”
Section: Introductionmentioning
confidence: 99%
“…DMF is non-official in BP, EP [2][3] and United States Pharmacopeia (USP) [4]. Literature review showed that few analytical methods have been described for the estimation of DMF including spectrophotometric [5][6], gas chromatography (GC) [7][8][9][10][11], high performance liquid chromatography (HPLC) [12][13][14][15][16][17], electrochemical and voltammetric methods [18] have been reported for the estimation of DMF in pure or in dosage forms.…”
Section: Introductionmentioning
confidence: 99%